PATIENTS WITH DECOMPENSATION OF CHRONIC PULMONARY HEART- REMODELING PARAMETERS OF THE RIGHT ATRIUM AND RIGHT VENTRICLE - A. K. Koyirov; S. R. Kenjaev; S. SH. Khaitov; U. SH. Ganiev; N. T. Egamova; M. S. Mirmaksudov (Евразийский Кардиологический Журнал)
Precapillary pulmonary hypertension (PH) encompasses a range of diseases characterized by a mean pulmonary arterial pressure of >25 mm Hg and a pulmonary arterial wedge pressure <15 mm Hg determined by right heart catheterization.1 The term «precapillary PH» may include group 1 (pulmonary arterial hypertension), group 3 (PH due to lung diseases and/or hypoxia), group 4 (chronic thromboembolic PH), and group 5 (PH associated with unclear or multifactorial mechanisms). Precapillary PH is associated with a rise in pulmonary vascular resistance that finally leads to right ventricular (RV) pressure overload and failure. The latter is associated with the high morbidity and mortality rates of the disease. In the past, the right ventricle has attracted most of the attention when assessing the impact of precapillary PH on the heart. Recently, however, focus has shifted toward the right atrium, with increased right atrial (RA) size included in the diagnostic and prognostic algorithms for patients with pulmonary arterial hypertension. The right atrium has a triple role in cardiac function: it acts as a reservoir, receiving deoxygenated blood from the venae cavae during ventricular systole; as a conduit that transfers blood through the tricuspid valve to the right ventricle during early diastole (passive RV filling); and as a pump that pushes blood to the right ventricle during late diastole (atrial contraction). 285 The role of the right atrium in contributing to cardiac output is well established in patients with precapillary PH and becomes manifest when patients go into atrial fibrillation, which can lead to acute decompensation. Purpose of the study - echocardiography parameters remodeling of the right atrium, RV in COPD patients with decompensating of CPH to evaluate correlation remodeling PKC with systolic, diastolic RV function.